(3GdebGeGJ (B((3GdMQjQjI(B)s - (3GdbGSe Hf Ydj Hf eMeO Hf YKeGf, CHh eMeO GdMQjQj GdHUQj , J (B516 (3g` s ((3LHd GdUGdMjf s)
(3ChdgG (B:s
(3hHYO, aEfg LQi HHYV CfOjI GdCOH GdPj QcOJ aj gPG GdYUQ QjMg s
(3BNQgG (B:s
(3hcGfJ gPg NGJeI GdJdGbj bGd GdTjN CHheMeO GdbGSe Hf Ydj, gPG BNQ GdebGeGJ s
(3GdfSNI HgG MhGTs
(3fSNI QGHYIs
(3HChdgG dhMI ePgHIs
(3hQO CjVkG JMJ Qbe (B2186 (3COH s
(3hHMhGTjgG HYV eYGfj GdCdaGX hChQGbgG eVWQHI GdJQJjHs
(3bQf GdfSN (B:s
Keywords: (3GdCOHs